2014
DOI: 10.1039/c3cp54922d
|View full text |Cite
|
Sign up to set email alerts
|

Spin density distribution after electron transfer from triethylamine to an [Ir(ppy)2(bpy)]+ photosensitizer during photocatalytic water reduction

Abstract: The photoreduction of the bis(2-phenylpyridinato-)(2,2'-bipyridine)iridium(III) ion ([Ir(ppy)2(bpy)](+)), used as a photosensitizer in photocatalytic water splitting, by triethylamine was studied by means of UV/VIS, XANES, and EPR spectroscopies, supported by theoretical calculations at density functional theory (DFT) and complete active space self-consistent field (CASSCF/CASPT2) levels. The combination of these methods suggests a predominant bpy localization of the spin-density of the unpaired electron with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 74 publications
4
52
0
Order By: Relevance
“…For the isolated reduced IrPS in the doublet electronic state, the unpaired electron was previously shown to be localized on π(bpy) * orbital. 91 For the IrPS−Ag 10 , the internal oxidationreduction occurs for ω > 0.25 bohr −1 : the unpaired electron moves from π(bpy) * to σ * (Ag). As IrPS forms no stable complexes, IrPS−X, neither with TEA nor with the iron-catalysts 89 , the relative position of constituents might be flexibly varied.…”
Section: Optimization Of the Rangeseparation Parametermentioning
confidence: 99%
“…For the isolated reduced IrPS in the doublet electronic state, the unpaired electron was previously shown to be localized on π(bpy) * orbital. 91 For the IrPS−Ag 10 , the internal oxidationreduction occurs for ω > 0.25 bohr −1 : the unpaired electron moves from π(bpy) * to σ * (Ag). As IrPS forms no stable complexes, IrPS−X, neither with TEA nor with the iron-catalysts 89 , the relative position of constituents might be flexibly varied.…”
Section: Optimization Of the Rangeseparation Parametermentioning
confidence: 99%
“…However, one example involving paramagnetic W(V) and Mo(V) species is important here [61]. The catalysts were prepared by dissolving the W/Mo chlorides in the ionic liquids (molar ratio between 1/10 and 1/100) and applied for hex-1-ene metathesis at r.t. For this purpose WCl 6 and MoCl 5 were dissolved in different ionic liquids (tetrafluoroborates of 1-ethyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, N-hexylpyridinium and 1-butyl-3-methylimidazolium, trihexyl(tetradecyl)phosphonium and 1-ethyl-3-methyl-imidazoolium). In the catalytic reactions oct-4-ene was formed as the main product, which means that fast isomerization of hex-1-ene to hex-2-ene takes place.…”
Section: Olefin Metathesis In Ionic Liquidsmentioning
confidence: 99%
“…Examples where the g-tensor can be misleading are some ligand-radical complexes of heavy transition metals such as iridium, for which SOC constants are large. In such cases even a small spin density at the metal can cause a substantial g-anisotropy, thus underlining the importance of combining EPR spectroscopy with DFT property calculations to determine spin density distributions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, on the basis of a multi-spectroscopic/computational study, the ppy ligand has been identified as being relevant for the properties of the first bright transition in IrPS, whereas the bpy ligand has been found to be important as an electron reservoir storing the electron after photoreduction by a sacrificial reductant [27]. Thus, chemical modification of these ligands separately could shed light on how these properties can be manipulated, thus paving the way for a rational design of future PSs.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we have explored ground and excited state properties of a series of Ir-based photosensitizers, which are derivatives of the parent IrPS extensively investigated before in catalytic, spectroscopic, and theoretical studies [11,[21][22][23][24][25][26][27][28][29][30][31][32][33]. To facilitate an accurate description of the excited states, the optimally-tuned range-separated density functional approach has been chosen.…”
Section: Discussionmentioning
confidence: 99%